Minat Belajar Siswa Dikelas Digital dalam Pembelajaran IPA (Fisika) di MTsN 4 Banda Aceh - Mahyana, Mahyana; Husnizar, Husnizar; Nurmalina, Nurmalina (Journal of Technology and Literacy in Education, 2024)
This study aims to observe students’ interest in participating in digital science (Physics) learning classes at MTsN 4 Banda Aceh. The research uses a quantitative approach with a descriptive method. The data to be collected is in numerical form, which will be statistically analyzed to describe students’ interest in digital science (Physics) learning in digital classrooms. This research was conducted at MTsN 4 Banda Aceh. Data was collected through observation and questionnaires. The data collected from the questionnaires was analyzed quantitatively using percentage analysis to depict the level of student interest. Based on the results of the study, it can be concluded that students’ interest in learning in digital science (Physics) classes at MTsN 4 Banda Aceh, based on four indicators in the interest questionnaire, obtained an average score of 78.21% in the high category.